A new species of Dibamus (Squamata: Dibamidae) from Phnom Samkos Wildlife Sanctuary, southwestern Cardamom Mountains, Cambodia - Neang, Thy; Holden, Jeremy; Eastoe, Toby; Seng, Rathea; Ith, Saveng; Grismer, L. Lee (Zootaxa, 2011)
A new species of legless lizard, Dibamus dalaiensis sp. nov. of the family Dibamidae is described from Phnom Dalai in Phnom Samkos Wildlife Sanctuary, southwestern Cardamom Mountains, Cambodia, based on the following unique combination of characters: maximum SVL 127.6 mm; tail 18–22% of SVL; a single postocular scale; three scales bordering the posterior edge of first infralabial; an enlarged, medial, sublabial scale; labial and nasal sutures complete; rostral suture present but incomplete; 20 midbody scale rows; 22 scale rows just posterior to head and 20 scale rows just anterior to vent; 185–209 ventrals; and 48–52 subcaudal scales. The discovery of D. dalaiensis sp. nov. represents a new family, genus and species record for Cambodia.